1979
DOI: 10.1029/ja084ia04p01261
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of ionosphere and troposphere during the occurrence of isolated tornadoes on November 20, 1973

Abstract: Gravity waves are the product of Joule heating, the auroral electrojet during geomagnetic substorms, the equatorial electrojet in the thermosphere, severe thunderstorms, tornadoes, and hurricanes in the troposphere, etc. A thorough understanding of sources and sinks of gravity waves can greatly advance our knowledge concerning atmosphere‐ionosphere‐magnetosphere couplings. We have limited ourselves in this paper to discussions of couplings between the ionosphere and the troposphere during the time periods of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These meteorological events are mostly distributed in the low-to mid-latitude and produce Atmospheric Gravity Waves (AGW) in the troposphere (Hung et al, 1979;Kelley, 1997;Laštovička, 2006;Xiao et al, 2007). The generated AGWs propagate upward and can disturb the ionosphere with a duration of hours (thunderstorm cells and tornadic storms) to even days (typhoon and cyclone).…”
Section: Discussionmentioning
confidence: 99%
“…These meteorological events are mostly distributed in the low-to mid-latitude and produce Atmospheric Gravity Waves (AGW) in the troposphere (Hung et al, 1979;Kelley, 1997;Laštovička, 2006;Xiao et al, 2007). The generated AGWs propagate upward and can disturb the ionosphere with a duration of hours (thunderstorm cells and tornadic storms) to even days (typhoon and cyclone).…”
Section: Discussionmentioning
confidence: 99%
“…Since these initial observations, the characteristics of TIDs have been investigated using a variety of techniques. These include (a) electron density measurements using vertical and oblique ionosondes (e.g., Afraimovich et al, ; Morgan et al, ; Ogawa et al, ; Tedd et al, ) and incoherent scatter radars (ISRs; e.g., Djuth et al, , ; Fukao et al, ; Nicolls & Heinselman, ), (b) backscatter radar soundings (e.g., Bristow et al, ; Bristow & Greenwald, ; Frissell et al, , ), (c) continuous wave (CW) Doppler measurements (e.g., Georges, ; Hung et al, ; Röttger, ), (d) total electron content (TEC) measurements using Global Positioning System (GPS) satellite constellations (e.g., Galushko et al, ; Nicolls et al, ; Onishi et al, ), and (e) optical airglow measurements (e.g., Kubota et al, ; Paulino et al, ; Shiokawa et al, , ). All of these measurement techniques have their strengths and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This said, there have been many other observations of MSTIDs suggesting tropospheric sources (e.g., Bishop et al, ; Davies & Baker, ; Davies & Jones, ; Frissell et al, ; Gossard, ; Hung & Kuo, ; Hung & Smith, ; Prasad et al, ). For example, Hung et al () observed MSTIDs using an HF Doppler sounder and determined that these MSTID events were associated with tornadoes via ray tracing and comparison with meteorology data. Waldock and Jones () determined the characteristics of MSTIDs observed using the HF Doppler technique over Leicester, UK.…”
Section: Introductionmentioning
confidence: 99%
“…The observations of gravity waves were also reported during tornadoes. Hung et al (1979) described observations of 1315 min and 2730 min waves in the ionospheric F region during an extreme tornado outbreak. Zuo Xiao et al (2007) observed medium scale travelling ionospheric disturbances with periods near 20 min which gradually grow longer and spread F after sunset as a response to a typhoon.…”
Section: Introductionmentioning
confidence: 99%